Analisis Collaborative Governance dalam Pengelolaan Aset Wakaf Sebagai Strategi Pengentasan Kemiskinan di Kota Parepare - Alfiyah Dhiyaul Auliyah; Andi Bahri S.; Islamul Haq; Hannani; Suarning (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the fundamental role of cross-sector collaborative governance in optimizing waqf asset management as a poverty alleviation strategy in Parepare City. Employing a qualitative field research design with an interpretative paradigm, primary data were collected through in-depth semi-structured interviews and non-participant observation involving key stakeholders, namely the Ministry of Religion, the Indonesian Waqf Board, and Nahdlatul Ulama's Philanthropic Institution (LAZISNU). The data were analyzed using an interactive qualitative model encompassing data condensation, display, and conclusion drawing. The research introduces the novelty of a Dual-Track Collaboration Model, demonstrating that state institutions predominantly focus on legal-defensive asset protection, while civil society autonomously drives productive community empowerment. Furthermore, the study identifies a Collaborative Capacity Gap, where facilitative leadership and external political support are constrained by the absence of local regulations and the centralized management of cash waqf funds. Consequently, this creates a paradox of Transitional Optimization based on Social Resilience. The current collaborative framework successfully secures socio-religious infrastructure and educational sustainability for vulnerable groups, yet it has not achieved immediate macroeconomic poverty alleviation due to regional fund outflows to the central government.